Nipah Virus Transmission Dynamics: Zoonotic Origins, Human Spread, and Control Strategies - John, Jeas; Anju Thomas; Rahul E (Gayaku Publisher, 2024)
A member of the Paramyxoviridae family, Nipah virus is one of the re-emerging viruses as a public health concern since it was first detected at the turn of the century in the late 1990s. Case fatality rates during outbreaks ranged between 40% and 75%, with recurrent cases in Bangladesh, India, and Malaysia. Surveillance data indicate the possibility of virus development in new areas since there is virus circulation among Pteropus bats in larger regions of South and Southeast Asia. It appears to be of zoonotic origin, transmitted mainly from fruit bats to humans. This makes zoonotic transmission a complex interaction between wildlife and human health, implying the significant role of ecology dynamics in the prevention and control of outbreaks. This understanding of routes of transmission has given basis to the devising of evidence-based interventions, including the protection of date palm sap collection sites and enhancement of infection prevention practices in hospitals, which will be very critical for controlling outbreaks and preventing future epidemics. This discussion on Nipah virus transmission dynamics calls for going into detail regarding the zoonotic source and mode of human-to-human transmission that enables human beings to prevent and control this disease.